மக்களை அணுகுதல் : வெகுசன ஊடகங்களின் நிகழ்ச்சி நிரல் மீதான விமர்சனப் பார்வை - Raguram, S. (Ministry of Mass Media, Government of Sri Lanka, 2019)
As we are living in a period in which the people have a huge expectation of the mass media, the critical view of mass media on the way the mass media approach the public becomes very important. Particularly; the authority people have on accepting and denying the information provided by the media, the limited ability of media to understand the people, usage of media language that can reach the public, the trust people have in media, the influence of owners of media on the media are the main platforms to which the critical view becomes necessary. The dominance and one-way communication approach, undue profits orientation and business motivation, interest in handling information for their own benefits, denial of a plural identity and effort made to create a single identity are the obstacles and drawbacks of media in reaching the general public and achieving its journalistic objectives. There is a need to have an insight into these drawbacks and obstacles and we must make efforts to strengthen the alternative communication platform from these points of view. In this respect, even though communication is for the people, mostly the social, economic, political and cultural influences mainly decide the way these people perceive the communication. This phenomenon can be considered as the natural defensive mechanism of the public to block the scope of communication or the media. This means blindly opposing media cannot be understood as getting protection from indiscriminate attacks of media, rather it should be healthy to take this as a mechanism to avoid unnecessary infiltration and damages caused by the media. Even though mass media is capable of providing information to a mass population quickly, it’s capability in catering and effectively reaching out grass-root people is widely questioned too.